The role of iron and zinc in cognitive development of children - Mamun, Md Abdullah Al; Ghani, Ruhina Binta A (Asian Journal of Medical and Biological Research, 2017)
The effects of iron and zinc on cognitive, motor and behavioral development are on children is scientifically accepted and concentrates on the more recent work, some previous work and areas of controversy. There are well established associations with poor development and iron and zinc deficiency in food source but the deficiencies usually occur in disadvantaged circumstances and establishing causal relationships is not easy. The health and well being of children depend upon the interaction between their genetic potential and exogenous factors like adequacy of nutrition, safety of the environment, social interaction and other childhood activity. Both proteins-energy malnutrition and micronutrient deficiencies increase the risk of death from common diseases such as acute gastroenteritis, pneumonia and measles. Iron deficiency anemia, for example, is estimated to affect almost 25% of the worlds population resulting in high economic cost by adding to the burden on health care services, affecting learning in school. Dietary practices frequently seen in children from both developed and developing countries, leading to frequent consumption of nutrient poor foods, may also put them at risk of micronutrient deficiencies. Asian J. Med. Biol. Res. June 2017, 3(2): 145-151